Sistem Pendukung Keputusan Penerimaan Karyawan dengan Metode Simple Additive Weighting Berbasis Website - Nabilla Aulia Nisa; Winarto (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2022)
Within the scope of an organization, human resources are needed. Human resources are used as organizational assets to improve the performance of their organizations, one of which is maintaining their company assets to continue to reform, namely by finding or recruiting new employees according to the needs of the company. Along with the times and industry competition, companies are expected to use technology to significantly increase efficiency and effectiveness so as to compete with other companies. One of the uses of technology to help the company's activities to be efficient and effective is the process of recruiting new employees by using online website-based technology information systems. The use of website-based information technology information systems is modeled in the model of multiple attribute decision making (MADM) which is to look for a number of alternatives to certain criteria and choose based on the best rankings. In MADM modeling there are several methods that are used as calculations, namely, Simple Additive Weighting Method (SAW), Weighted Product (WP), ELECTRE, Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), and Analytic Hierarchy Process (AHP). The decision support system in this study uses the Simple Additive Weighting Method (SAW)method. In this case, prospective new employees will be compared to each other in each assessment of criteria and sub-criteria and weight values that have been determined by the company. The results of this system that has been designed result in a decision support system to determine who the prospective employees who qualify in the administrative stage